PENGARUH CHATGPT TERHADAP KOMPETENSI DAN PERILAKU MAHASISWA: TINJAUAN LITERATUR - Diah, Halimahtusya; Arum, Enggar Diah Puspa (Jurnal Akuntansi Kompetif, 2026)
This study employs a Systematic Literature Review to investigate the impact of ChatGPT on the competencies and behavior of accounting students. Fifteen national and international journal articles published between 2020 and 2025 were reviewed using sources from Google Scholar and ResearchGate. The findings suggest that ChatGPT can support learning by improving technical skills, analytical thinking, digital literacy, and independent study through interactive assistance. However, overreliance on this technology may also create challenges, such as reduced critical thinking, technological dependence, and potential academic dishonesty. These outcomes reflect both opportunities and risks in shaping future human capital in the accounting profession. Therefore, the use of ChatGPT in accounting education should be carefully managed. Beyond adopting advanced technology, educators need to emphasize digital ethics, responsible behavior, and professional values to ensure the development of competent, ethical, and integrity-driven future accountants.